Characterization of the complete plastid genome of Clivia mirabilis (Amaryllidaceae) - Ling Yue; Xiu-Li Feng; Dan Li; Hai-Hong Wu; Jing Meng; Xing-Hua Zhao (Mitochondrial DNA. Part B. Resources)
Clivia mirabilis Rourke 2002 is an evergreen herbaceous flower with high ornamental value. In this study, we sequenced the complete chloroplast (cp) genome of C. mirabilis and reported it for the first time. The cp genome was 158,914 base pairs (bp) in total length, including two inverted repeats (IRs, 27,052 bp), separated by a large single-copy region (LSC, 86,519 bp) and a small single-copy region (SSC, 18,291 bp). There are 133 different genes in the cp genome of Clivia mirabilis, including 87 protein-coding genes, 38 transfer RNA genes, and eight ribosomal RNA genes. The overall GC content of the cp genome was 37.9%. Our phylogenetic analysis showed that C. mirabilis formed a monophyletic clade with the other sampled species of Clivia, falling into the Amaryllidoideae clade. Our findings could be used to identify and analyze the genetic diversity of C. mirabilis and provide new data for taxonomic and phylogenetic studies of Clivia.